2012
DOI: 10.1210/jc.2011-1801
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Scan for Loci of Adolescent Obesity and Their Relationship with Blood Pressure

Abstract: Genome-wide association studies conducted in an adolescent founder population revealed two new and a number of previously identified loci of obesity and demonstrated that several but not all of these loci are also associated with elevated BP. These results begin to reveal the genetic architecture of obesity-induced hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 19 publications
0
44
1
1
Order By: Relevance
“…In the case of BP, neither Freathy et al [25] nor Kring et al [26] observed an association; however, Pausova et al [39] did otherwise with systolic BP in adolescents. Moreover, a recent genome-wide scan identified an association between rs9930333 (SNP in LD with rs9939609) and BP in adolescents [40]. In our study population, the percentage of MS in the obese group was 9.8%, and we did not observe association of any SNPs with MS (data not shown).…”
Section: Discussionmentioning
confidence: 44%
“…In the case of BP, neither Freathy et al [25] nor Kring et al [26] observed an association; however, Pausova et al [39] did otherwise with systolic BP in adolescents. Moreover, a recent genome-wide scan identified an association between rs9930333 (SNP in LD with rs9939609) and BP in adolescents [40]. In our study population, the percentage of MS in the obese group was 9.8%, and we did not observe association of any SNPs with MS (data not shown).…”
Section: Discussionmentioning
confidence: 44%
“…Genome-wide Association Studies (GWAS) have made significant headway in identifying genetic variants underlying obesity (Cotsapas et al , 2009; Meyre et al , 2009; Jiao et al , 2011; Paternoster et al , 2011; Wang et al , 2011; Melka et al , 2012; Pei et al , 2014; Locke et al , 2015). However, most of these studies focused on body mass index as the main outcome, failing to take into consideration behavioral differences that can precede the development of obesity.…”
Section: Introductionmentioning
confidence: 99%
“…The minor alleles of the three SNPs that were nominally associated with a protective role against preeclampsia development in our study have previously been associated with BP regulation [25,26,28]. These SNPs are located in or close to the ATP2B1 , PAX5 , and PLCD3 genes.…”
Section: Discussionmentioning
confidence: 72%